2002
DOI: 10.1021/ma0204913
|View full text |Cite
|
Sign up to set email alerts
|

A Small-Angle Neutron and X-ray Contrast Variation Scattering Study of the Structure of Block Copolymer Micelles:  Corona Shape and Excluded Volume Interactions

Abstract: Small-angle neutron and X-ray scattering data have been obtained for micelles of d-polystyrene−polyisoprene (d-PS−PI) of relatively high molecular weight in n-decane. Contrast variation was performed using mixtures of hydrogenated and deuterated decane. Three samples were investigated with d-polystyrene and polyisoprene molar masses of, respectively, 12 000 and 48 000, 40 000 and 40 000, and 40 000 and 80 000. For the two latter samples, the concentration of the polymer was also varied. The data obtained at re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
214
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 156 publications
(234 citation statements)
references
References 59 publications
16
214
0
Order By: Relevance
“…3. We estimated the radius of gyration of the polymer layer, s, of SiNP-PMAPS and SiNP-PMPC from the SAXS profile using a core-shell model analysis, taking the interacting excluded-volume chains into consideration 23) and assuming the corona chains as infinitely thin perturbed wormlike chains. 24) Figure 4 shows the C s -dependence of s and R H,brush for SiNP-PMAPS ( ) and SiNP-PMPC ( ) in aqueous NaCl solutions, where R H,brush were obtained by DLS measurements.…”
Section: Chain Dimension Of Free Ionic Polymers In Solutionmentioning
confidence: 99%
“…3. We estimated the radius of gyration of the polymer layer, s, of SiNP-PMAPS and SiNP-PMPC from the SAXS profile using a core-shell model analysis, taking the interacting excluded-volume chains into consideration 23) and assuming the corona chains as infinitely thin perturbed wormlike chains. 24) Figure 4 shows the C s -dependence of s and R H,brush for SiNP-PMAPS ( ) and SiNP-PMPC ( ) in aqueous NaCl solutions, where R H,brush were obtained by DLS measurements.…”
Section: Chain Dimension Of Free Ionic Polymers In Solutionmentioning
confidence: 99%
“…In this section, it will be shown that the phenomenological evolution of the SANS data can be quantitatively reproduced with an additive model of free chains (RPA) and of an adaptation of the Pedersen model for hairy micelles 60,61 . The form factor of the latter is mimicked by a sphere with Gaussian chains on the surface.…”
Section: Iii2 Modeling Of Sans Data Of Pure H-d-matricesmentioning
confidence: 99%
“…This model describes the detailed structural features of the starlike micelles considering both the internal PEP core and the outer PEO shell. In order to account for some slight structure factor effects at the highest concentration, we employed Percus-Yevick structure factor which is shown to give good results for dilute block copolymer micelles [24]. Some fit results are shown in Fig.…”
mentioning
confidence: 99%